Branched triphenylamine luminophores: Aggregation-induced fluorescence emission, and tunable near-infrared solid-state fluorescence characteristics via external mechanical stimuli. (April 2018) - Zhu, Huichao; Huang, Jianyan; Kong, Lin; Tian, Yupeng; Yang, Jiaxiang
Abstract: Three AIE-active branched luminophores (defined as4a, 4b and4c ) containing triphenylamine and carbazole units forming intramolecular charge transfer (ICT) states have been developed. The studies of the mechanical stimuli effect on solid state showed that the branch number can affect effectively the performance of the tunable fluorescence in the solid state. Interestingly, only compound4a displayed a distinct bathochromic shift of its fluorescence emission from the visible (λem  = 598 nm) to the near-infrared section (λem  = 643 nm) by mechanical stimuli. Moreover, 4a exhibited an obvious crystallization-induced emission enhancement (CIEE) effect. The crystal samples of4a emit strong orange light with 49.8% solid-state fluorescence quantum yield ( Ф F ) and the amorphous showed decreased red emission with 7.6% ( Ф F ). Mechanical grinding and organic solvent stimuli can reversibly change the phase transition between crystalline and amorphous states. However, compounds4b and4c are not sensitive to the mechanical stimuli, because it is difficult for them to form crystalline structure due to bigger steric hindrance effect. The mechanism for their solid-state fluorescence behavior was investigated in detail by powder X-ray diffraction (PXRD), scanning electron microscopy (SEM) and differential scanning calorimetry (DSC) analysis. Graphical abstract: Three AIE-active branched luminophores (defined as4a, 4b and4c ) containing triphenylamine and carbazole units forming intramolecular charge transfer (ICT) states have been developed. The results showed that the branch number can affect effectively the performance of the tunable fluorescence in the solid state. Only compound4a displayed a tunable solid-state fluorescence emission at near-infrared section and an obvious crystallization-induced emission enhancement (CIEE) effect with 49.8% Ф F . Highlights: Three AIE-active branched luminophores containing triphenylamine and carbazole units with ICT states have been developed. Three compound are excellent fluorescence materials at long wavelength, especially4a with a high fluorescence efficiency (49.8%). Compound4a displayed a tunable solid-state fluorescence emission between the visible and the near-infrared section by mechanical stimuli, along with a CIEE effect. The results showed that the branch number can influence the performance of the tunable fluorescence emission behavior.